Chitosan nanoparticle and pyridoxine seed priming improves tolerance to salinity in milk thistle seedling - Ali Asghar MOSAVIKIA; Seyed Gholamreza MOSAVI; Mohammadjavad SEGHATOLESLAMI; Reza BARADARAN (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2020)
Application of growth regulators plays important role under salt conditions. Perspectives to overcome these limitations by chitosan nanoparticle (CSNP: 0, 0.25, 0.5, and 1%) and pyridoxine (PN: 0, 0.03, 0.06, and 0.09%) seed priming was studied in both experiments with milk thistle seeds exposed to NaCl as salt stress (0, 50, 100, and 150 mM). Salinity threshold and EC50 (the salinity level that 50% of germination reduction) achieved 74.85 and 213.5 mM, respectively. A significant reduction in germination percentage (49.12%), seedling length (50.07%), and seedling vigor index (67.39%) while, a significant increase in superoxide dismutase activity (54.63%) were achieved at 150 mM NaCl in compared to the control treatment. The highest germination rate was resulted by 100 mM NaCl and 0.25% CSNP and the least (2.86 seed/day) by 150 mM NaCl and without CSNP. The salt stress significantly decreased photosynthetic pigments; however, the largest value of chlorophyll a, b, and total was related to without NaCl and 1% CSNP and the least value of traits (6.1, 1.67, and 7.77 µg/g FW) to non-application of CSNP under 150 mM NaCl. PN application was caused decrease in free proline content compared to the non-application treatment. The most pronounced effects of CSNP and PN were recorded in 0.25 and 0.09% concentrations, respectively. The finding of this study leads to the conclusion that seed priming with CSNP and PN by improving physiological mechanisms such as photosynthetic pigment synthesis, antioxidant enzyme activities, and free proline content increased salt tolerance in milk thistle seedling.